Plagiarism Checker Data Indexing Technology for Indian Regional Language - Kumar H.M, Prashanth; Bhat S, Subramanya (International Journal of Computer Sciences and Engineering, 2023)
Plagiarism is considered a serious academic and ethical offense, as it undermines the values of originality, honesty, and integrity in academic and creative work. India has a diverse linguistic landscape, with over 22 official languages and many more regional languages spoken across the country. Several Indian states have taken steps to promote regional language education in recent years. In this case study we are exposing a very accurate plagiarism checker for all Indian regional languages. We are facing many challenges to develop this sort of software. So, mainly the data indexing methods are very interesting in this case. Here we are exposing how data indexing methodology works using ‘Taylor series’ formula in cloud-based storage for Indian regional languages.